Autophagy and epithelial–mesenchymal transition: an intricate interplay in cancer - Gugnoni, Mila (Cell Death Dis, 2016)
Autophagy and epithelial to mesenchymal transition (EMT) are major biological processes in cancer. Autophagy is a catabolic pathway that aids cancer cells to overcome intracellular or environmental stress, including nutrient deprivation, hypoxia and drugs effect. EMT is a complex transdifferentiation through which cancer cells acquire mesenchymal features, including motility and metastatic potential. Recent observations indicate that these two processes are linked in a complex relationship. On the one side, cells that underwent EMT require autophagy activation to survive during the metastatic spreading. On the other side, autophagy, acting as oncosuppressive signal, tends to inhibit the early phases of metastasization, contrasting the activation of the EMT mainly by selectively destabilizing crucial mediators of this process. Currently, still limited information is available regarding the molecular hubs at the interplay between autophagy and EMT. However, a growing number of evidence points to the functional interaction between cytoskeleton and mitochondria as one of the crucial regulatory center at the crossroad between these two biological processes. Cytoskeleton and mitochondria are linked in a tight functional relationship. Controlling mitochondria dynamics, the cytoskeleton cooperates to dictate mitochondria availability for the cell. Vice versa, the number and structure of mitochondria, which are primarily affected by autophagy-related processes, define the energy supply that cancer cells use to reorganize the cytoskeleton and to sustain cell movement during EMT. In this review, we aim to revise the evidence on the functional crosstalk between autophagy and EMT in cancer and to summarize the data supporting a parallel regulation of these two processes through shared signaling pathways. Furthermore, we intend to highlight the relevance of cytoskeleton and mitochondria in mediating the interaction between autophagy and EMT in cancer.